Heavy metals concentrations in river Benue, Adamawa State, Nigeria - Sarah Danzaria Mshelia (PANGAEA, 2021)
This study was designed to assess the concentration of heavy metals in water, two fish species (Clarias gariepinus and Oreochromis niloticus), and three different vegetables (Spinach, Rosella, and Jute mallow) which were grown around the riverbank of River Benue. A laboratory-based study was adopted. Fish, water samples, and vegetables were collected monthly at different locations named points A, B, and C from River Benue for five consecutive months between October 2019 and February 2020 and analyzed for physicochemical parameters. The parameters included pH, dissolved oxygen (DO), temperature, conductivity, lead, cadmium, manganese, zinc, Iron, and copper.